2022
DOI: 10.3390/en15020528
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Integrated Photovoltaic-Thermal and Air Source Heat Pump System through Energy Simulation

Abstract: The concept of zero energy buildings (ZEBs) has recently been actively introduced in the building sector, globally, to reduce energy consumption and carbon emissions. For the implementation of ZEBs, renewable energy systems, such as solar collectors, photovoltaic (PV) systems, and ground source heat pump (GSHP) systems, have been used. The system performance of solar collectors and PV systems are dependent on the weather conditions. A GSHP system requires a large area for boring machines and mud pump machines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Another researcher used an existing building to perform heating and cooling analysis for one year using the dynamic simulation model. As the simulation analysis results, the average coefficient of performance (COP) for the heating season was 5.3, and the average COP for the cooling season was 16.3, respectively [13]. Beyond the performance of the PVT-HP system enhanced, the system was also economically feasible and shortened the payback period compared to the standalone systems [14].…”
Section: Introductionmentioning
confidence: 87%
“…Another researcher used an existing building to perform heating and cooling analysis for one year using the dynamic simulation model. As the simulation analysis results, the average coefficient of performance (COP) for the heating season was 5.3, and the average COP for the cooling season was 16.3, respectively [13]. Beyond the performance of the PVT-HP system enhanced, the system was also economically feasible and shortened the payback period compared to the standalone systems [14].…”
Section: Introductionmentioning
confidence: 87%
“…Kong et al [19] presented the appropriate number of PV/T modules through a performance analysis and an economic comparison of PV/T-cascade heat pumps for cooling and heating periods in tropical climates. Bae et al [20] found that a PV/T-ASHP system installed in a small building improved heating and cooling performance coefficients by 52% compared to an ASHP system used alone. They also demonstrated that the electricity generated by the PV/T modules during certain periods exceeded the system's power consumption, making it possible to achieve a fully zero-energy building [21].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [18] used numerical simulation and experimental heat transfer characterization in square aluminium tubes to remove thermal heat from the system and boost the electrical efficiency of an air PV/T collector. A significant amount of current research has been conducted in the last 2 years that focuses on the ways of installing PV/T solar collectors in buildings, which essentially centres on the study of heat gain, power consumption, and PV/T module lifetime [19][20][21].…”
Section: Introductionmentioning
confidence: 99%